European style electoral politics in an ethnically divided society. The case of Kosovo - Wise Laura; Agarin Timofey (Comparative Southeast European Studies, 2017)
Our paper takes as its starting point the premise that elections are central moments in the life of polities: these are the times when individual citizens demonstrate support or otherwise of political institutions and regimes, assess their accountability and set agendas for the next government. In short, elections allow us to observe whether and how political regimes live up to society’s expectations. This issue has particular resonance in deeply divided societies that have experienced ethnic conflict in the past. In the deeply divided society of Kosovo, local and national elections in 2013 and 2014 presented an opportunity to analyze voter choices and elite agendas, with the presence of ethnopolitical issues under scrutiny. Our paper concludes that the normalization of electoral politics, within the context of European aspirations, has not yet taken place in Kosovo, and that the options available to the electorate continue to be dominated by identity politicking.